2010
DOI: 10.1158/0008-5472.can-09-2995
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Tumor Necrosis Factor α Signaling in Tumor-Associated Macrophages as a Radiosensitizing Strategy

Abstract: Most cancer patients receive radiotherapy during the course of their disease.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
147
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(155 citation statements)
references
References 47 publications
8
147
0
Order By: Relevance
“…This is mediated by a release of various cytokines, superoxide, and nitric oxide (8). All of which are capable of causing tissue damage (22) by signaling through pro-apoptosis mediator TNF-␣, Fas ligand, nitric oxide, and superoxide (23,24).…”
Section: Radiation-induced Bystander Responses (Rbr)mentioning
confidence: 99%
See 1 more Smart Citation
“…This is mediated by a release of various cytokines, superoxide, and nitric oxide (8). All of which are capable of causing tissue damage (22) by signaling through pro-apoptosis mediator TNF-␣, Fas ligand, nitric oxide, and superoxide (23,24).…”
Section: Radiation-induced Bystander Responses (Rbr)mentioning
confidence: 99%
“…TNF-␣ is a pro-inflammatory cytokine whose expression is known to be highly up-regulated in many tissues and cells after IR (23,25). TNF-␣ is a 17-kDa polypeptide that specifically binds and exerts its function via two cell surface receptors, TNFR1 (p55) and TNFR2 (p75).…”
Section: Radiation-induced Bystander Responses (Rbr)mentioning
confidence: 99%
“…19 In vivo , it is rather difficult to assess the direct effect of IR on macrophage activation. However, recent studies in the tumor stroma showed that high doses of IR (> 8Gy) promote anti-inflammatory activation of macrophages, 20 and low doses (< 2Gy) combined with immunotherapy induce proinflammatory activation of macrophages that favor tumor elimination. 21 These data suggest that there is a direct effect of IR on macrophage activation.…”
Section: Macrophage Response To Radiotherapymentioning
confidence: 99%
“…On the other hand, ionizing radiation can also generate chemotactic signals that recruit several myeloid-cell types with distinct roles in T cell suppression (114)(115)(116).…”
Section: Multimodality Treatments and Future Directionsmentioning
confidence: 99%